Microstructure and mechanical properties of oxide dispersion strengthened high-entropy alloys CoCrFeMnNi and CrFe₂MnNi - Kolodiy, I.V.; Velikodnyi, O.M.; Tikhonovsky, M.A. (Вопросы атомной науки и техники, 2021)
High-entropy alloys (HEAs) CoCrFeMnNi and CrFe₂MnNi, dispersion-strengthened by pre-synthesized nanooxides composition of 80%Y₂O₃+20%ZrO₂ (mol.%) were obtained by mechanical alloying followed by compaction and sintering. Average grain size of the oxide dispersion-strengthened (ODS) alloys was about 2 μm. Oxide precipitates in alloys are characterized by the presence of small particles with an average size of about 10 nm and a density of ≈ 10²¹ m⁻³, as well as small amount of larger particles sizes of 50…150 nm. The qualitative composition of particles of different sizes has been established. Mechanical properties of HEAs were studied at different temperatures. It is shown that strengthening of the studied alloys by nanooxide particles leads to a significant increase in strength characteristics.